Modeling of Self-Concept and Work Stress in Women Personnel of Semnan University of Medical Sciences: Mediated Role of Religious Orientation - s safaee; M ghiasi; A Jafari Nodoushan; h Kakaei; R Jafari Nodoushan (طب کار)
Introduction: Employees are often faced with some stressful situations that with their self-concept content, affect their job satisfaction, mental and physical health. Also, religious orientation plays an important role. The aim of this study was to examine the mediating role of religious orientation in relation to the self-concept of job stress.